FIGURE 7 in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 7. Chitonaster trangae nov. sp. Holotype USNM E13585. A. Abactinal Surface. B. Actinal surface. USNM 1121466 C. Granules on abactinal arm surface. USNM E13503. D. Coelomic view of abactinal plates showing papular pores. USNM E50555-E. Lateral view of marginal plates and abactinal spines. F. Abactinal spines and plate variation. Scale Bar = 0.5 cm. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 18, DOI: 10.5281/zenodo.276783